The Influence of Social Media on Students' Mathematical Creative Thinking Skills - Priyanto, Rizky; Septian, Ari; Monariska, Erma (PRISMA, 2025)
This research endeavors to scrutinize the mathematical creative thinking proficiencies of students and to ascertain the extent to which social media engagement impacts these abilities. The methodological framework employed herein is quantitative, adopting a descriptive research design, with data collection facilitated via survey instruments. The cohort for this investigation comprised 33 students enrolled in class X APHP at SMK Negeri 1 Pacet. To measure mathematical creative thinking skills, a test instrument was used, while social media usage was measured using a non-test instrument, namely a questionnaire. The collected data was then analysed using statistical tests with a quantitative approach, namely regression and quantitative descriptive tests. The empirical findings reveal that the aggregate mathematical creative thinking capacity among the students at SMK Negeri 1 Pacet registers at 73.5%, positioning it within a high classification. Nevertheless, a more granular examination indicates a positive correlation between social media utilization and mathematical creative thinking acumen; however, this association is characterized by diminutive strength and lacks statistical significance. Consequently, these results suggest that social media does not exert a substantial influence on the enhancement of mathematical creative thinking skills among the student population at SMK Negeri 1 Pacet.